2019
DOI: 10.1016/j.molcel.2019.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and Persistent 8-Oxoguanine Base Damage at Telomeres Promotes Telomere Loss and Crisis

Abstract: Highlights d Targeted chronic 8-oxoG damage at telomeres promotes telomere shortening d Unrepaired telomeric 8-oxoG in OGG1-deficient cells impairs telomere replication d 8-oxoG-induced telomere losses cause dicentric chromosomes and anaphase bridges d Persistent telomeric 8-oxoG drives telomere crisis and global genomic instability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
214
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(238 citation statements)
references
References 81 publications
(101 reference statements)
16
214
0
1
Order By: Relevance
“…Although we report TL shortening at 18 months of age in both brain and heart tissue, previous research using zebrafish has not observed age-dependent differences in TL until fish are at least 2 years of age (41,70).Furthermore, others have shown no TL effect of age in the brain of zebrafish (39). Failure to detect telomere shortening in brain tissues could be a consequence of the lower rate of cell renewal and neurogenesis in the adult brain compared to heart making detection difficult (39,63,69).The lack of consistency in zebrafish findings highlights possible differences in the technique used to assess telomere length, on the rate of telomere attrition between strains (40,41) and animal facilities, which should all be carefully considered. Furthermore, we have combined data from a sibling populations of young and ageing zebrafish, thus allowing for samples to be processed simultaneously, which assures similar storage time and reagents used, critical consideration for the study of telomere biology (71).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although we report TL shortening at 18 months of age in both brain and heart tissue, previous research using zebrafish has not observed age-dependent differences in TL until fish are at least 2 years of age (41,70).Furthermore, others have shown no TL effect of age in the brain of zebrafish (39). Failure to detect telomere shortening in brain tissues could be a consequence of the lower rate of cell renewal and neurogenesis in the adult brain compared to heart making detection difficult (39,63,69).The lack of consistency in zebrafish findings highlights possible differences in the technique used to assess telomere length, on the rate of telomere attrition between strains (40,41) and animal facilities, which should all be carefully considered. Furthermore, we have combined data from a sibling populations of young and ageing zebrafish, thus allowing for samples to be processed simultaneously, which assures similar storage time and reagents used, critical consideration for the study of telomere biology (71).…”
Section: Discussionmentioning
confidence: 48%
“…When this peak is weakened by stress-related hormones (25,41,56) it may diminish their ability to counteract injuries thus leading to shorter telomeres and the associated increased risk of cardiomyopathies. However, our research cannot rule out a telomerase-independent process resulting from a chronically activated HPI axis, such as the postulated direct effect of reactive oxygen species (63). Nonetheless, the present investigation shows that zebrafish are a promising animal to model cardiomyopathies in ageing individuals.…”
Section: Discussionmentioning
confidence: 65%
“…Our test results of SOD and MDA found that SMCs in different dose groups can increase the SOD value of cells treated with ox-LDL and decrease the MDA value. SOD and MDA are classic indicators of oxidative stress evaluation, and there are currently reports in the literature that oxidative stress can promote cellular senescence [42][43][44]. Studies show that oxidative stress accelerate telomere shortening or dysfunction and telomere shortening suppresses cancer by triggering senescence in normal cells [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) modifies DNA bases, most commonly resulting in 8-oxoguanine (8-oxoG) and thymine glycol (Tg) (125). If not repaired, 8-oxoG induces GC-TA transversion mutations as well as single-strand or double-strand breaks, leading to genomic instability (126). Tg is the most prevalent oxidative product of thymine, responsible for 10 -20% of ionizing radiation-induced genomic damage (127).…”
Section: Telomere Proteins and Their Role In The Genome-wide Responsementioning
confidence: 99%